A situação ocupacional dos jovens no Brasil: 2002 a 2012 - Ciríaco, Juliane da Silva (2015)
Concerning the transition from school to work, there is in the country a marked number of young people outside the labor market and educational system, called generation "nem-nem". Because of that, this dissertation aims to investigate from two independent trials this population subgroup, considering the age range 18-25 years using as a data source PNAD (Pesquisa Nacional por Amostra de Domicílios). The first test aims to determine the main determinants of the condition "nem-nem" in Brazil, in the period between 2002 and 2012, except for 2010 (year of the Censo). To this end, the Logistic model will be applied, considering the complex sample design of the PNAD. The estimation results indicated that having another young "nem-nem" with same age in the family tends to increase by more than 2/5 the probability of the young be provided "nem-nem". Besides the variables of family background and education of the young were crucial in determining the group "nem-nem", reinforcing the idea that a favorable family environment is key to reducing the rates of employment and educational inactivity among young people. Another interesting result is related to the number of retired elderly in the family, little explored in other current research observed in the area. It is observed that the biggest holding of retired elderly within the family tends to increase the likelihood of young to be simultaneously outside the labor market as well as the school system. The second test, in turn, is proposed empirically analyze the main determinants of the condition "nem-nem" in Brazil (here represented by an indicator called juvenile exclusion rate) differential considering the sex, emphasizing the influence of the effect of social context in determining the occupational status of the young. For this, it uses an innovative way Multilevel Logistic methodological framework for 2002 and 2012, incorporating the hierarchical nature of the data at individual and aggregate. The main results indicated the importance of the social environment in determining the condition "nem-nem" in the country in order to evaluate the degree of extent of influence between environments, verified by the value of the coefficient of intra-class correlation (ICC), which although reduced It should not be disregarded. Last year, the value found in the ICC blank template for men and women in due order corresponds to 0,0184 and 0,0571 indicating that 1,84% and 5,71% of the variance in youth exclusion rate can be attributed for the environment. It is inferred that for men contextual variables were important in determining the condition "nem-nem", represented by the variable Index Gini and Total "nem-nem", both with positive effects. For women, the results showed that the condition "nem-nem" is directly related to family income, education and presence of children in the family. Thus, this study reinforces the importance of clear and visible youth develop consistent policies, which can be enhanced through investments to crèches and generating higher employment and income for the Brazilian population.